Implementasi Sistem QR Code Dalam Meningkatkan Tingkat Kepatuhan Pengisian Checklist Pemeriksaan Kendaraan Harian di PT XYZ: Studi Komparatif Sebelum dan Sesudah Penerapan - Muhammad Helmy Ilhamsyah; Felixtianus Eko Wismo Winarto; Lilik Dwi Setyana; Nur Rokhman (LKP Unity Academy, 2025)
Daily vehicle inspection is an important component of risk control in occupational safety and health (OSH) management systems. However, manual inspection processes often result in low compliance in checklist completion, reporting delays, and limited monitoring capabilities. This study aims to analyze the effect of implementing a QR Code system on the compliance level of daily vehicle inspection checklist completion at PT XYZ. The study employed a quasi-experimental design with a one-group pretest-posttest approach involving 35 operational vehicles. Data were collected from vehicle inspection checklists before and after the implementation of the QR Code system and analyzed using descriptive and inferential statistics through a paired sample t-test. The results showed that the compliance level increased from 72.2% before implementation to 90.2% after the implementation of the QR Code system. Statistical testing indicated a significant difference in compliance levels before and after implementation with t(34)=26.7 and p<0.001. An effect size value of 4.52 indicated a very large effect on compliance improvement. The implementation of the QR Code system proved effective in improving checklist completion, strengthening monitoring processes, and supporting the digitalization of occupational safety and health management systems in operational environments.